2017
DOI: 10.1093/hmg/ddx009
|View full text |Cite
|
Sign up to set email alerts
|

KLF13 is a genetic modifier of the Holt-Oram syndrome gene TBX5

Abstract: TBX5, a member of the T-box family of transcription factors, is a dosage sensitive regulator of heart development. Mutations in TBX5 are responsible for Holt-Oram Syndrome, an autosomal dominant disease with variable and partially penetrant cardiac defects suggestive of the existence of genetic and environmental modifiers. KLF13, a member of the Krüppel-like family of zinc finger proteins is co-expressed with TBX5 in several cardiac cells including atrial cardiomyocytes and cells of the interatrial septum. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 32 publications
4
39
0
1
Order By: Relevance
“…Previously, we showed that KLF13 and TBX5 exhibit physical and functional interactions and that a combined heterozygous loss of TBX5 and its associated KLF13 leads to decreased postnatal viability and a higher incidence of septal defects compared to that of Tbx5 heterozygous mice. Additionally, several TBX5 mutations have been associated with CHDs, as indicated by impaired functional and physical interactions with KLF13, which confirms that TBX5 is a genetic cofactor of KLF13 [9]. In the present study, the increased transcriptional activity of BNP was more pronounced when wild-type KLF13 was cotransfected with TBX5, which indicated that KLF13 has functional interactions with TBX5 to activate BNP promoters.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Previously, we showed that KLF13 and TBX5 exhibit physical and functional interactions and that a combined heterozygous loss of TBX5 and its associated KLF13 leads to decreased postnatal viability and a higher incidence of septal defects compared to that of Tbx5 heterozygous mice. Additionally, several TBX5 mutations have been associated with CHDs, as indicated by impaired functional and physical interactions with KLF13, which confirms that TBX5 is a genetic cofactor of KLF13 [9]. In the present study, the increased transcriptional activity of BNP was more pronounced when wild-type KLF13 was cotransfected with TBX5, which indicated that KLF13 has functional interactions with TBX5 to activate BNP promoters.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, the increased transcriptional activity of BNP was more pronounced when wild-type KLF13 was cotransfected with TBX5, which indicated that KLF13 has functional interactions with TBX5 to activate BNP promoters. In our previous study of the structure-function of TBX5-KLF13 synergy [9], the N-terminal domain of KLF13 was mainly found to support synergy with TBX5. The two variants of KLF13 that were detected in the 309 CHD patients were in the N-terminal domain of the protein.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations